Manufacturing method of rotor type compressor slip sheet without compound layer
The compound layer of the slide sheet is eliminated through the compound-free layer process and the wear-resistant coating is coated with a vapor deposition process, which solves the problem of insufficient friction loss of the slide sheet and insufficient coating bonding power in the new environmentally friendly refrigerant environment, and achieves the efficient wear resistance of the slide sheet and the improvement of the compressor energy efficiency.
Patent Information
- Application Number
- CN202311314020.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-11
- Publication Date
- 2025-03-04
AI Technical Summary
The friction loss of the existing compressor slide plate is intensified under the new environmentally friendly refrigerant environment. The original surface treatment technology cannot meet the needs. The high-hard wear-resistant coating and the slide substrate have little bonding force. The coating falls off or wears after long-term use, which affects the energy efficiency and service life of the compressor.
The surface strengthening of the compressor slide is carried out using the compound-free layer process to eliminate the fragile and peeling compound layers, and directly perform a vapor deposition process to coat the wear-resistant coating to improve the bonding force between the slide and the coating.
In a high load-bearing, high impact and high-speed friction environment, the bond strength of the slide coating and the substrate is improved, and the coating is not easy to fall off, which extends the service life of the compressor slide and improves the energy efficiency of the compressor.
Abstract
Description
Technical Field
[0001] The invention relates to a rotary compressor component, in particular to a compressor vane. Background Art
[0002] The main body of the rotor type air conditioning compressor is mainly composed of a rotating piston and a stator. The stator is a cylinder body, and the rotor is eccentrically placed in the stator. There is a vane between the rotor and the cylinder body. The cylinder volume on both sides of the vane changes due to the rotation of the rotor, thereby completing the continuous suction and compression of the medium. Vane compressors are widely used because of their simple structure, high efficiency, convenient operation and maintenance, quiet operation, and low vibration.
[0003] As the core component of the compressor, the vane needs to be in close contact with the eccentric rolling piston of the compressor. The shape, size, surface finish, hardness and nitriding layer of the compressor vane need to be determined according to the requirements of the application. At present, the vane manufacturing generally cuts out the vane substrate first, and then the vane substrate undergoes a series of treatments to obtain a qualified vane. There is a mature manufacturing method for processing the vane substrate into a qualified vane. From the appropriate material to the formed vane, corresponding cutting, heat treatment, nitriding, fine grinding, etc. are performed to meet the requirements of the shape, precision, matrix hardness and surface hardness of the vane, such as the methods disclosed in Chinese patent documents CN1424510A, CN101629573A, CN102251167A, CN102251166A, CN103206379A, etc.
[0004] Due to environmental protection requirements, domestic and foreign air conditioning companies have started using new refrigerants such as R744, R32, R410A and other environmentally friendly new refrigerants in high-efficiency air conditioners to replace traditional Freon substances such as R22. Environmentally friendly new refrigerants are mainly composed of hydrogen, fluorine and carbon elements, and have the characteristics of stability and non-toxicity. At the same time, since they do not contain fluorine elements, they will not damage the ozone layer. In addition, air conditioners using environmentally friendly new refrigerants have also improved in performance. Therefore, environmentally friendly new refrigerants are currently internationally recognized as the most suitable refrigerants to replace oral refrigerants and have been used so far.
[0005] However, due to the use of environmentally friendly new refrigerants, the original compressors and their spare parts can no longer fully meet the new refrigerant medium environment requirements, including the internal working pressure of the compressor, which has increased from 1.5Mpa~2Mpa in R22 to 3Mpa~4Mpa in R410A, and even some refrigerant use environments have reached more than 20Mpa. Therefore, in the new refrigerant environment, the wear of the "heart component" of the compressor, the vane, has intensified, and the original surface treatment technology of the vane can no longer meet the needs. It is necessary to coat the vane with a coating through physical vapor deposition (PVD), chemical vapor deposition (CVD), plasma enhanced chemical vapor deposition (PECVD) and other coating methods to increase the surface hardness of the vane and reduce the wear of the vane. However, these methods are costly, and the vane coating has a weak bonding force with the metal matrix. It is in a boundary lubrication state for a long time. After the coating falls off or wears off, the long-term reliability of the vane cannot be guaranteed. At the same time, the coating falls off or wears off will aggravate the change in the size of the vane, increase the refrigerant leakage, and reduce the energy efficiency of the compressor.
[0006] The prior art believes that: the introduction of high-hardness wear-resistant coatings requires good bonding between the vane and the coating. For high-hardness wear-resistant coatings, the vane needs to be surface hardened to improve the surface hardness of the vane, thereby improving the good bonding between the vane and the coating. Generally, before depositing a thin film on the surface of the vane substrate, the vane substrate is optimized for surface nitriding pretreatment, including nitriding, carbonitriding, and oxygen-nitrogen-carbon ternary nitriding technology, to improve the hardness of the vane substrate, so that the vane substrate and the coating have a higher matching, thereby improving the bonding between the two. But in fact, the existing nitrided vane surface must produce a compound layer, but because the compound layer has high hardness and high brittleness, it is not conducive to the bonding between the vane substrate and the high-hardness wear-resistant coating, especially under high load and high pressure, the compound layer will produce brittle collapse, and then the coating attached to the surface will peel off together, resulting in coating failure, further accelerating the wear of the compressor and shortening its service life. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the above-mentioned deficiencies of the prior art and provide a method for manufacturing a compound layer compressor vane, so that the vane manufacturing is more convenient and efficient, and the wear-resistant coating is more firmly bonded.
[0008] The technical solution adopted by the present invention to solve the above problems is: A method for manufacturing a compound layer-free rotor compressor vane, characterized in that it comprises the following steps: 1): Select suitable metal materials to machine the compressor vane substrate; 2): Using a compound-free layer process to perform surface strengthening on a compressor vane substrate to obtain a compressor vane substrate after surface strengthening; 3): A wear-resistant coating is applied to the surface of the compressor vane substrate obtained in step 2) by using a vapor deposition process to prepare a wear-resistant coating that meets the requirements of an air-conditioning compressor, thereby obtaining a qualified compressor vane.
[0009] The process of eliminating the compound layer in step 2) is a process of eliminating the surface nitriding of the compound layer.
[0010] The compound-free layer process in step 2) is controlled gas nitriding, and the conditions are: The process parameters of the first stage are: ammonia gas flow rate is 5m 3 / h; temperature rises from room temperature to 320℃-350℃ within 2-3h; The process parameters of the second stage are: temperature 320-350℃, holding time 5-7h, ammonia flow rate 5-7m 3 / h; The process parameters of the third stage are: heating from 320-350℃ to 560℃-590℃ for 1-2h; The process parameters of the fourth stage are: temperature 560-590℃, holding time 4-6h, total ammonia flow rate 5-7m 3 / h, where the ratio of ammonia gas to cracked ammonia is in the range of 1:4~1:6; The process parameters of the fifth stage are: temperature drops from 560-590℃ to 280-300℃, time is 1-3h, total ammonia flow rate is 5-7m 3 / h, where the ratio of ammonia gas to cracked ammonia is in the range of 1:4~1:6; The process parameters of the sixth stage are: stop supplying ammonia, vent with nitrogen, and the flow rate is 20-30m 3 / h, and then cooled to 80-100℃ along with the furnace.
[0011] Preferably, the wear-resistant coating in step 3) is a carbon-based coating.
[0012] Preferably, the wear-resistant coating in step 3) is, in sequence: a pure metal layer, a metal nitride layer, and a carbon-based coating.
[0013] Preferably, the wear-resistant coating in step 3) is sequentially: a pure metal layer, a metal nitride layer, another metal nitride layer, and a carbon-based coating.
[0014] More specifically, the metal is chromium (Cr).
[0015] More specifically, the another metal nitride layer is tungsten nitride (WN).
[0016] Preferably, the metal material is martensitic or austenitic stainless steel.
[0017] More preferably, the carbon-based coating includes a diamond-like carbon-based coating (DLC) and a graphite-like carbon-based coating (GLC).
[0018] Compared with the prior art, the advantages of the present invention are: the compound layer produced in the existing nitriding process has high hardness and is extremely brittle. It is very easy to collapse brittlely in the environment of high load, high impact and high-speed friction. After the coating process, the collapse will occur together with the surface coating, resulting in coating failure and aggravated wear, and finally causing product failure. Since the present invention treats the compressor vane through a compound layer-free process, the fragile and easy-to-peel compound layer of the treated compressor vane can be directly eliminated during the nitriding process, and then the vane can maintain the bonding strength between the coating and the vane substrate in the internal environment of the compressor with high load, high impact and high-speed friction, thereby improving the service life of the compressor vane. After the compressor vane is subjected to conventional means such as usual cleaning, the next step of coating the wear-resistant coating can be directly carried out, which not only simplifies the step of removing the compound layer in the compressor vane after nitriding treatment by mechanical processing in the prior art, but also improves the bonding strength between the compressor vane and the wear-resistant coating, making it difficult to fall off during use. Therefore, the preparation method of the present invention is simpler, more efficient, and the quality of the compressor vane obtained is higher. Implementation
[0019] The present invention is further described in detail below with reference to the embodiments.
[0020] A method for manufacturing a compound layer-free rotor compressor vane, characterized in that it comprises the following steps: 1): Select suitable metal materials to machine the compressor vane substrate; 2): Using a compound-free layer process to perform surface strengthening on a compressor vane substrate to obtain a compressor vane substrate after surface strengthening; 3): A wear-resistant coating is applied to the surface of the compressor vane substrate obtained in step 2) by using a vapor deposition process to prepare a wear-resistant coating that meets the requirements of an air-conditioning compressor, thereby obtaining a qualified compressor vane.
[0021] Since compressor vanes are already standardized products, their shapes and specifications have been finalized, and conventional technical means have been disclosed in a large number of patent documents. For details, please refer to these patent documents and will not be described in detail here. The present invention only discloses its main improvements as follows, which are as follows: The surface nitriding process of the compound-free layer of the present invention can be carried out by using a conventional nitriding furnace or by using a special nitriding furnace, and is characterized in that the treatment conditions are used.
[0022] The compound-free layer nitriding treatment in step 2) described in this embodiment is controllable gas nitriding, and the treatment conditions are detailed in the embodiments.
[0023] The compressor vane obtained by the above nitriding treatment has no compound layer, which is conducive to the next step of plating wear-resistant coating.
[0024] The coating equipment for coating the wear-resistant coating of the present invention can adopt a PVD and PECVD composite coating machine, which includes a vacuum chamber, a vacuum pump, a molecular pump, a gas source, an arc source, a magnetron sputtering source, a radio frequency power supply, a microwave generator, and a workpiece bracket that can simultaneously revolve and rotate. The workpiece bracket is installed inside the vacuum chamber, and a high-purity single substance (purity> 99.9%) target material is installed on the arc source and the magnetron sputtering source. Other similar equipment can also be used.
[0025] The preparation conditions are detailed in the examples. Example 1
[0026] A method for manufacturing a compound layer-free rotor compressor vane comprises the following steps: 1): Select austenitic stainless steel to machine the compressor vane substrate; 2): Using a compound-free surface nitriding process to strengthen the surface of the compressor vane substrate to obtain a compressor vane substrate with a strengthened surface; 3): A wear-resistant coating is applied to the surface of the compressor vane substrate obtained in step 2) by using a vapor deposition process to prepare a wear-resistant coating that meets the requirements of an air-conditioning compressor, thereby obtaining a qualified compressor vane.
[0027] The conditions in step 2) are: The process parameters of the first stage are: ammonia gas flow rate is 5m 3 / h; temperature rises from room temperature to 320℃ within 2h; The process parameters of the second stage are: temperature 320℃, holding time 7h, ammonia flow rate 5m 3 / h; The process parameters of the third stage are: heating from 320°C to 560°C for 1 h; The process parameters of the fourth stage are: temperature 560℃, holding time 4h, total ammonia flow rate 5m 3 / h, where the ratio of ammonia gas to cracked ammonia is 1:5; The process parameters of the fifth stage are: temperature drops from 560℃ to 280℃, time is 1h, total ammonia flow rate is 5m 3 / h, where the ratio of ammonia gas to cracked ammonia is 1:5; The process parameters of the sixth stage are: stop supplying ammonia, vent with nitrogen, and the flow rate is 20m 3 / h, and then cooled to 80℃ in the furnace.
[0028] The obtained compressor sliding vane substrate compound layer was 0.
[0029] The preparation conditions of step 3) are: 1) Heating and vacuuming the plating chamber The temperature rises to 100°C and the vacuum degree is 2.0×10 -5 mbar; 2) Compressor vane etching Inert gas was introduced, microwave power was 1500W, bias current of compressor vane was 9A, and working time was 20 minutes; 3) Compressor vane coating pure metal Cr base layer Prepared by physical vapor deposition process, the voltage of metal Cr target material was increased by 25KW, 500sccm of inert gas was introduced, the bias current of compressor vane was 5A, and the working time was 20 minutes; 4) Compressor vane coated with diamond-like functional layer The plasma enhanced chemical vapor deposition process was used for preparation, with 1300 sccm acetylene, 2000 W microwave power, 5 A bias current of the compressor vane, and 20 minutes of operation time;
[0030] 5) Allow air to flow in and cool to room temperature in the furnace to complete the preparation of the diamond-like coating on the surface of the compressor vane.
[0031] The compressor vane coating prepared is 3.5 microns thick and bright black in color. The film-base bonding strength of the film is measured to be over 40N, the friction coefficient is below 0.08, and the nanoindentation hardness is over 21GPa. Example 2
[0032] A method for manufacturing a compound layer-free rotor compressor vane comprises the following steps: 1): Select martensitic stainless steel to machine the compressor vane substrate; 2): Using a compound-free surface nitriding process to strengthen the surface of the compressor vane substrate to obtain a compressor vane substrate with a strengthened surface; 3): A wear-resistant coating is applied to the surface of the compressor vane substrate obtained in step 2) by using a vapor deposition process to prepare a wear-resistant coating that meets the requirements of an air-conditioning compressor, thereby obtaining a qualified compressor vane.
[0033] The conditions in step 2) are: The process parameters of the first stage are: ammonia gas flow rate is 5m 3 / h; temperature rises from room temperature to 350℃ within 3h; The process parameters of the second stage are: temperature 350℃, holding time 5h, ammonia flow rate 5m 3 / h; The process parameters of the third stage are: heating from 350°C to 590°C for 2 h; The process parameters of the fourth stage are: temperature 590℃, holding time 6h, total ammonia flow rate 5m 3 / h, where the ratio of ammonia gas to cracked ammonia is 1:6; The process parameters of the fifth stage are: temperature drops from 590℃ to 280℃, time is 4h, total ammonia flow rate is 5m 3 / h, where the ratio of ammonia gas to cracked ammonia is 1:6 The process parameters of the sixth stage are: stop supplying ammonia, vent with nitrogen, and the flow rate is 20m 3 / h, and then cooled to 80℃ in the furnace.
[0034] The obtained compressor sliding vane substrate compound layer was 0.
[0035] The preparation conditions of step 3) are: 1) Heating and vacuuming the plating chamber The temperature rises to 100-200℃, and the vacuum degree is 2.0×10 -5 mbar; 2) Compressor vane etching Inert gas was introduced, the microwave power of the ion source was ≥1500W, the bias current of the compressor vane was 9A, and the working time was 30 minutes; 3) Compressor vane coating pure metal Cr base layer Prepared by physical vapor deposition process, the voltage of metal Cr target material is increased by more than 20KW, 500-800 sccm of inert gas is introduced, the bias current of compressor vane is 5A, and the working time is 10 minutes; 4) Compressor vane coating metal nitride CrN base layer Prepared by physical vapor deposition process, the metal target voltage is increased by 22KW, 600sccm of inert gas and 400sccm of high-purity N2 are introduced, the bias current is 5A, and the working time is 20 minutes; 5) Compressor vane coated with diamond-like functional layer The preparation was carried out by plasma enhanced chemical vapor deposition process, with 1200 sccm of acetylene, 2000 W of microwave power, 3-5 A of bias current of compressor vane, and 30 minutes of working time.
[0036] 6) Allow air to flow in and cool to room temperature in the furnace to complete the preparation of the diamond-like coating on the surface of the compressor vane.
[0037] The compressor vane film produced has a thickness of 3.8 microns and is bright black. The film-base bonding strength is measured to be over 40N, the friction coefficient is below 0.08, and the nanoindentation hardness is over 21GPa. Example 3
[0038] A method for manufacturing a compound layer-free rotor compressor vane comprises the following steps: 1): Select austenitic stainless steel to machine the compressor vane substrate; 2): Using a compound-free surface nitriding process to strengthen the surface of the compressor vane substrate to obtain a compressor vane substrate with a strengthened surface; 3): A wear-resistant coating is applied to the surface of the compressor vane substrate obtained in step 2) by using a vapor deposition process to prepare a wear-resistant coating that meets the requirements of an air-conditioning compressor, thereby obtaining a qualified compressor vane.
[0039] The conditions in step 2) are: The process parameters of the first stage are: ammonia gas flow rate is 5m 3 / h; temperature rises from room temperature to 320℃ within 2h; The process parameters of the second stage are: temperature 320℃, holding time 5h, ammonia flow rate 7m 3 / h; The process parameters of the third stage are: heating from 320°C to 570°C for 1 h; The process parameters of the fourth stage are: temperature 570℃, holding time 4h, total ammonia flow rate 7m 3 / h, where the ratio of ammonia gas to cracked ammonia is 1:4; The process parameters of the fifth stage are: temperature drops from 570℃ to 300℃, time is 3h, total ammonia flow rate is 7m 3 / h, where the ratio of ammonia gas to cracked ammonia is 1:4; The process parameters of the sixth stage are: stop supplying ammonia, vent with nitrogen, and the flow rate is 30m 3 / h, and then cool to 100℃ in the furnace.
[0040] The obtained compressor sliding vane substrate compound layer was 0.
[0041] The preparation conditions of step 3) are: 1) Heating and vacuuming the plating chamber The temperature rises to 200℃ and the vacuum degree is 2.0×10 -5 mbar; 2) Compressor vane etching Inert gas was introduced, microwave power was 1600W, bias current of compressor vane was 6A, and working time was 20 minutes; 3) Compressor vane coating pure metal Cr base layer Prepared by physical vapor deposition process, the voltage of metal Cr target material was increased by 20KW, 500sccm of inert gas was introduced, the bias current of compressor vane was 3A, and the working time was 5 minutes; 4) Compressor vane coating metal nitride CrN base layer Prepared by physical vapor deposition process, the metal target voltage is increased by 20KW, 800sccm of inert gas and 200 of high-purity N2 are introduced, the bias current is 3-5A, and the working time is 15 minutes; 5) Compressor vane coating metal nitride WN transition layer Prepared by physical vapor deposition process, the metal target voltage is increased by 20KW, 300sccm of inert gas and 400sccm of high-purity N2 are introduced, the bias current is 3-5A, and the working time is 30 minutes; 6) Compressor vane coated with diamond-like functional layer The preparation was carried out by plasma enhanced chemical vapor deposition process, with more than 1300 sccm of acetylene introduced, microwave power of 2000 W, bias current of compressor vane of 3 A, and working time of 30 minutes.
[0042] 7) Allow air to flow in and cool to room temperature in the furnace to complete the preparation of the diamond-like coating on the surface of the compressor vane.
[0043] The compressor vane film produced has a thickness of 3.9 microns and is bright black. The film-base bonding strength is measured to be over 40N, the friction coefficient is below 0.08, and the nanoindentation hardness is over 21GPa. Example 4
[0044] A method for manufacturing a compound layer-free rotor compressor vane comprises the following steps: 1): Select martensitic stainless steel to machine the compressor vane substrate; 2): Using a compound-free surface nitriding process to strengthen the surface of the compressor vane substrate to obtain a compressor vane substrate with a strengthened surface; 3): A wear-resistant coating is applied to the surface of the compressor vane substrate obtained in step 2) by using a vapor deposition process to prepare a wear-resistant coating that meets the requirements of an air-conditioning compressor, thereby obtaining a qualified compressor vane.
[0045] The conditions in step 2) are: The process parameters of the first stage are: ammonia gas flow rate is 5m 3 / h; temperature rises from room temperature to 330℃ within 3h; The process parameters of the second stage are: temperature 330℃, holding time 6h, ammonia flow rate 5m 3 / h; The process parameters of the third stage are: heating from 330°C to 580°C for 2h; The process parameters of the fourth stage are: temperature 580℃, holding time 5h, total ammonia flow rate 5m3 / h, where the ratio of ammonia gas to cracked ammonia is 3:17; The process parameters of the fifth stage are: temperature drops from 580℃ to 300℃, time is 2 h, total ammonia flow rate is 5m 3 / h, where the ratio of ammonia gas to cracked ammonia is 3:17; The process parameters of the sixth stage are: stop supplying ammonia, vent with nitrogen, and the flow rate is 20m 3 / h, and then cooled to 80℃ in the furnace.
[0046] The obtained compressor sliding vane substrate compound layer was 0.
[0047] The preparation conditions of step 3) are: 1) Heating and vacuuming the plating chamber The temperature rises to 120℃ and the vacuum degree is 2.0×10 -5 mbar; 2) Compressor vane etching Inert gas was introduced, microwave power was 1800W, compressor vane bias current was 8A; 3) Compressor vane coating pure metal Cr base layer Prepared by physical vapor deposition process, the metal target voltage is increased by 22KW, 650sccm of inert gas is introduced, the bias current is 4A, and the working time is 15 minutes; 4) Compressor vane coating metal nitride CrN base layer Prepared by physical vapor deposition process, the metal target voltage is increased by 22KW, 500sccm of inert gas and 400sccm of high-purity N2 are introduced, the bias current is 4A, and the working time is 15 minutes; 5) Compressor vane coating metal nitride WN transition layer Prepared by physical vapor deposition process, the metal target voltage is increased by 22KW, 300sccm of inert gas and 400sccm of high-purity N2 are introduced, the bias current is 4A, and the working time is 30 minutes; 6) Compressor vane coated with diamond-like functional layer The preparation was carried out by plasma enhanced chemical vapor deposition process, with 1000 sccm of acetylene, 2000 W of microwave power, 4 A of bias current, and a working time of 30 minutes.
[0048] 7) Allow air to flow in and cool to room temperature in the furnace to complete the preparation of the diamond-like coating on the surface of the compressor vane.
[0049] The compressor vane film prepared has a thickness of 4.0 microns and is bright black. The film-base bonding strength is measured to be above 40N, the friction coefficient is below 0.08, and the nanoindentation hardness is above 21GPa. Example 5
[0050] A method for manufacturing a compound layer-free rotor compressor vane comprises the following steps: 1): Select martensitic stainless steel to machine the compressor vane substrate; 2): Using a compound-free surface nitriding process to strengthen the surface of the compressor vane substrate to obtain a compressor vane substrate with a strengthened surface; 3): A wear-resistant coating is applied to the surface of the compressor vane substrate obtained in step 2) by using a vapor deposition process to prepare a wear-resistant coating that meets the requirements of an air-conditioning compressor, thereby obtaining a qualified compressor vane.
[0051] The conditions in step 2) are: The process parameters of the first stage are: ammonia gas flow rate is 5m 3 / h; temperature rises from room temperature to 330℃ within 3h; The process parameters of the second stage are: temperature 330℃, holding time 6h, ammonia flow rate 5m 3 / h; The process parameters of the third stage are: heating from 330°C to 580°C for 2h; The process parameters of the fourth stage are: temperature 580℃, holding time 5h, total ammonia flow rate 5m 3 / h, where the ratio of ammonia gas to cracked ammonia is 3:17; The process parameters of the fifth stage are: temperature drops from 580℃ to 300℃, time is 2 h, total ammonia flow rate is 5m 3 / h, where the ratio of ammonia gas to cracked ammonia is 3:17; The process parameters of the sixth stage are: stop supplying ammonia, vent with nitrogen, and the flow rate is 20m 3 / h, and then cooled to 80℃ in the furnace.
[0052] The obtained compressor sliding vane substrate compound layer was 0.
[0053] The preparation conditions of step 3) are: 1) Heating and vacuuming the plating chamber The temperature rises to 120℃ and the vacuum degree is 2.0×10 -5 mbar; 2) Compressor vane etching Inert gas was introduced, microwave power was 1800W, compressor vane bias current was 8A; 3) Compressor vane coating pure metal Cr base layer Prepared by physical vapor deposition process, the metal target voltage is increased by 22KW, 650sccm of inert gas is introduced, the bias current is 4A, and the working time is 15 minutes; 4) Compressor vane coating metal nitride CrN base layer Prepared by physical vapor deposition process, the metal target voltage is increased by 22KW, 500sccm of inert gas and 400sccm of high-purity N2 are introduced, the bias current is 4A, and the working time is 15 minutes; 5) Compressor vane coating metal nitride WN transition layer Prepared by physical vapor deposition process, the metal target voltage is increased by 22KW, 300sccm of inert gas and 400sccm of high-purity N2 are introduced, the bias current is 4A, and the working time is 30 minutes; 6) Compressor vane coating with graphite-like carbon coating (GLC) functional layer The target was prepared by magnetron sputtering with pure graphite target, 650sccm of inert gas was introduced, the bias current was 5A, and the working time was 20 minutes.
[0054] 7) Air is introduced and the furnace is cooled to room temperature to complete the preparation of the graphite-like carbon-based coating (GLC) on the surface of the compressor vane.
[0055] The compressor vane film prepared is 4.5 microns thick and bright black in color. The film-base bonding strength is measured to be over 40N, the friction coefficient is below 0.06, and the nanoindentation hardness is over 15GPa.
Claims
1. A method for manufacturing a compound layer-free rotor compressor vane, characterized in that: The following steps are involved: 1): Select suitable metal materials to machine the compressor vane substrate; 2): Using a compound-free layer process to perform surface strengthening on a compressor vane substrate to obtain a compressor vane substrate after surface strengthening; 3): A wear-resistant coating is applied to the surface of the compressor vane substrate obtained in step 2) by using a vapor deposition process to prepare a wear-resistant coating that meets the requirements of an air-conditioning compressor, thereby obtaining a qualified compressor vane.
2. The method for manufacturing a compound layer-free rotor compressor vane according to claim 1, characterized in that: The process of eliminating the compound layer in step 2) is a process of eliminating the surface nitriding of the compound layer.
3. The method for manufacturing a compound layer-free rotor compressor vane according to claim 2, characterized in that: The compound-free layer process in step 2) is controlled gas nitriding, and the conditions are: The process parameters of the first stage are: ammonia gas flow rate is 5m 3 / h; temperature rises from room temperature to 320℃-350℃ within 2-3h; The process parameters of the second stage are: temperature 320-350℃, holding time 5-7h, ammonia flow rate 5~7m 3 / h; The process parameters of the third stage are: heating from 320-350℃ to 560℃-590℃ for 1-2h; The process parameters of the fourth stage are: temperature 560-590℃, holding time 4-6h, total ammonia flow rate 5~7m 3 / h, where the ratio of ammonia gas to cracked ammonia is in the range of 1:4~1:6; The process parameters of the fifth stage are: the temperature drops from 560-590℃ to 280-300℃, the time is 1-3 hours, and the total flow rate of ammonia is 5~7m 3 / h, where the ratio of ammonia gas to cracked ammonia is in the range of 1:4~1:6; The process parameters of the sixth stage are: stop supplying ammonia, vent with nitrogen, and the flow rate is 20~30m 3 / h, and then cooled to 80-100℃ along with the furnace.
4. The method for manufacturing a compound layer-free rotor compressor vane according to claim 1, characterized in that: The wear-resistant coating in step 3) is a carbon-based coating.
5. The method for manufacturing a compound layer-free rotor compressor vane according to claim 4, characterized in that: The wear-resistant coating structure in step 3) is: pure metal layer, metal nitride layer, carbon-based coating.
6. The method for manufacturing a compound layer-free rotor compressor vane according to claim 4, characterized in that: The wear-resistant coating structure in step 3) is: a pure metal layer, a metal nitride layer, another metal nitride layer, and a carbon-based coating.
7. The method for manufacturing a compound layer-free rotor compressor vane according to claim 4, 5 or 6, characterized in that: The metal is: chromium.
8. The method for manufacturing a compound layer-free rotor compressor vane according to claim 5 or 6, characterized in that: Another metal nitride is: tungsten nitride.
9. The method for manufacturing a compound layer-free rotor compressor vane according to claim 1, characterized in that: The metal materials are martensitic and austenitic stainless steels.
10. The carbon-based coating according to claim 4, characterized in that: The carbon-based coating includes a diamond-like carbon-based coating or a graphite-like carbon-based coating.
Citation Information
Patent Citations
Slip sheet of refrigeration compressor and manufacturing method thereof
CN101629573A
Manufacture method of slip sheet of air conditioner compressor
CN102251166A
Manufacture method of slip sheet of air conditioner compressor
CN102251167A
Sliding vane used in rotary compressor, and manufacturing method thereof
CN103206379A
Production for sliding vane of compressor
CN1424510A